Disease Severity Determines Timing of Initiating Continuous Renal Replacement Therapies: A Systematic Review and Meta-Analysis - Xia, Zi-Jing; He, Lin-ye; Pan, Shu-Yue; Cheng, Rui-Juan; Zhang, Qiu-Ping; Liu, Yi (Frontiers in Medicine, 2021)
Background: Timing of initiating continuous renal replacement therapies (CRRTs) among the patients with acute kidney injury (AKI) in intensive care units (ICU) has been discussed over decades, but the definition of early and late CRRT initiation is still unclear. Methods: The English language randomized controlled trials (RCTs) and cohort studies were searched through MEDLINE, EMBASE, and Cochrane Library on July 19, 2019, by the two researchers independently. The study characteristics; early and late definitions; outcomes, such as all-cause, in-hospital, 28- or 30-, 60-, 90-day mortality; and renal recovery were extracted from the 18 eligible studies. Pooled relative risk ratios (RRs) and 95% CIs were estimated with the fixed effects model and random effects model as appropriate. This study is registered with PROSPERO (CRD 42020158653). Results: Eighteen studies including 3,914 patients showed benefit in earlier CRRT (n = 1,882) over later CRRT (n = 2,032) in all-cause mortality (RR 0.78, 95% CI 0.66–0.92), in-hospital mortality (RR 0.81, 95% CI 0.67–0.99), and 28- or 30-day mortality (RR 0.81, 95% CI 0.74–0.88), but in 60- and 90-day mortalities, no significant benefit was observed. The subgroup analysis showed significant benefit in the disease-severity-based subgroups on early CRRT initiation in terms of in-hospital mortality and 28- or 30-day mortality rather than the time-based subgroups. Moreover, early CRRT was found to have beneficial effects on renal recovery after CRRT (RR 1.21, 95% CI 1.01–1.45). Conclusions: Overall, compared with late CRRT, early CRRT is beneficial for short-term survival and renal recovery, especially when the timing was defined based on the disease severity. CRRT initiation on Acute Kidney Injury Network (AKIN) stage 1 or Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE)-Risk or less may lead to a better prognosis.